2020
DOI: 10.1194/jlr.ra119000307
|View full text |Cite
|
Sign up to set email alerts
|

Of mice and men: murine bile acids explain species differences in the regulation of bile acid and cholesterol metabolism

Abstract: Compared with humans, rodents have higher synthesis of cholesterol and bile acids (BAs) and faster clearance and lower levels of serum LDL-cholesterol. Paradoxically, they increase BA synthesis in response to bile duct ligation (BDL). Another difference is the production of hydrophilic 6-hydroxylated muricholic acids (MCAs), which may antagonize the activation of FXRs, in rodents versus humans. We hypothesized that the presence of MCAs is key for many of these metabolic differences between mice and humans. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 36 publications
6
56
0
1
Order By: Relevance
“…In rodents, there are additional bile acids, the α-and β-muricholic acids (MCA), generated in the liver from CDCA [19,20]. These bile acids represent the product of specific murine gene, Cyp2c70, which is absent in human, and as such Cyp2c70 −/− mice present a bile "humanized" bile acid profile [20][21][22]. Accordingly, the T conjugated of α-and β-MCA are primary bile acids in mice, while ω-MCA, generated from the two MCAs in the intestine, is a secondary bile acid.…”
Section: H Nhch2ch2so3hmentioning
confidence: 99%
“…In rodents, there are additional bile acids, the α-and β-muricholic acids (MCA), generated in the liver from CDCA [19,20]. These bile acids represent the product of specific murine gene, Cyp2c70, which is absent in human, and as such Cyp2c70 −/− mice present a bile "humanized" bile acid profile [20][21][22]. Accordingly, the T conjugated of α-and β-MCA are primary bile acids in mice, while ω-MCA, generated from the two MCAs in the intestine, is a secondary bile acid.…”
Section: H Nhch2ch2so3hmentioning
confidence: 99%
“…The Cyp2c70, Cytochrome P450 family 2 subfamily c polypeptide 70, has been identified has the gene responsible for MCAs generation in rodents. [47][48][49][50] Cyp2c70 catalyzes the production of βMCA from CDCA by a two-step reaction involving first the 6β-hydroxylation of CDCA, producing α-MCA, followed by epimerization of the C7 hydroxyl group from the α to the β orientation, which generates β-MCA, In the present study, we have also shown that the liver expression of Cyp2c70 is severely blunted in Gpbar1 −/− mice, highlighting a putative regulatory mechanism for GPBAR1 on this gene. [47][48][49][50] Importantly, we have also shown that BAR501, a GPBAR1 ligand, and BAR704, a FXR ligand, both increase the liver expression of Cyp2c70 in wild-type mice ( Figure 5B), highlighting a potential role of the two receptors in regulating MCAs synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…To prove this concept, we have examined the liver expression of several FXR-regulated genes 46 and found that Shp, a FXR target gene, was significantly upregulated by fasting Gpbar1 −/− mice, while Cyp27a1, which mediates the first and limiting step in the alternative pathway of bile acid synthesis, that is mainly involved in generating CDCA, the precursor of α-and β-MCA acid, was downregulated ( Figure 1E). Furthermore, Gpbar1 −/− mice exposed to fasting were characterized by a dramatically reduction in the expression of Cyp2c70, which, in mice, is responsible for the synthesis of MCAs from CDCA [47][48][49][50] ( Figure 1E). Together, these results supported the notion that Gpbar1 gene ablation causes a dysregulated FXR signaling in the liver.…”
Section: Fasting-induced Autophagy Is Impaired By Gpbar1 Gene Ablationmentioning
confidence: 99%
“…In addition, experimental animals and humans have very different physiological indicators and disease tolerance, which may lead to incorrect conclusions. For example, mice and humans regulate bile acid and cholesterol metabolism differently [ 187 ], and human atherosclerotic plaques are more likely to rupture than those of mice [ 188 ]. These differences may lead to changes in the role of Nrf2 in human CCVD.…”
Section: Discussionmentioning
confidence: 99%